2009
DOI: 10.1093/icesjms/fsp066
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of batch fecundity and spawning fraction for the southern stock of horse mackerel (Trachurus trachurus) in ICES Division IXa

Abstract: Gonçalves, P., Costa, A. M., and Murta, A. G. 2009. Estimates of batch fecundity, and spawning fraction for the southern stock of horse mackerel (Trachurus trachurus) in ICES Division IXa. – ICES Journal of Marine Science, 66: 617–622. Since 1995 the annual egg production method has been applied triennially to the southern stock of horse mackerel (Trachurus trachurus) in the Northeast Atlantic (ICES Division IXa). This method assumes that fecundity is determinate, but increasing evidence indicates that horse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This difference in the spawning frequency may rely on geographical, ecological and behavioural differences as happens in other species like the sardine, Sardina pilchardus and horse mackerel, Trachurus trachurus. For this species, Gonçalves et al (2009) reported spawning frequency from 4.9 to 13.2 days in different months of spawning season for the Iberian coast stock while for Greek waters, Karlou-Riga and Economidis (1997) mentioned values of 5.8 and 4.8 for two successive reproductive periods. In fact, and according to these authors, spawning frequency may change from year to year and therefore might be another adaptive response to unfavourable conditions occurring within the spawning season.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This difference in the spawning frequency may rely on geographical, ecological and behavioural differences as happens in other species like the sardine, Sardina pilchardus and horse mackerel, Trachurus trachurus. For this species, Gonçalves et al (2009) reported spawning frequency from 4.9 to 13.2 days in different months of spawning season for the Iberian coast stock while for Greek waters, Karlou-Riga and Economidis (1997) mentioned values of 5.8 and 4.8 for two successive reproductive periods. In fact, and according to these authors, spawning frequency may change from year to year and therefore might be another adaptive response to unfavourable conditions occurring within the spawning season.…”
Section: Discussionmentioning
confidence: 92%
“…The estimated relative batch fecundity (22 ± 17 oocytes per gram of individual) is low when compared to other indeterminate species such as Trachurus trachurus (Gonçalves et al 2009), Engraulis mordax (Hunter et al 1985), Merluccius merluccius , Sardina pilchardus (Zwolinski et al 2001) and even with the same species living in the waters of the Canary Islands (García-Díaz et al 2006). However, the prolonged spawning season and the short interval between batches may compensate for the comparatively low batch fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…), and for still others the basic biology is insufficiently known to allow estimation (Gonçalves et al . ). It is relatively easy to measure fecundity of fishes with synchronous or group‐synchronous oocyte development.…”
Section: Introductionmentioning
confidence: 97%
“…Fecundity was estimated as batch fecundity (defined as the number of oocytes spawned per batch) for each specimen using the gravimetric method combined with image analysis as explained by . This estimation facilitates the measurement (diameter in μm) and the count of the oocytes in a subsample of a given weight (predefined arbitrarily approximately at 0.05 g to reduce any size effect of the subsample between estimates) taken from the central region of the ovary (Kraus et al 2005, Gonçalves et al 2009, Witthames et al 2009). Batch fecundity (F B ) was estimated according to with the formula…”
Section: Methodsmentioning
confidence: 99%